Redovisningsinnovationers spridning inom den offentliga sektorn : En studie om spridning och antagande av komponentavskrivning inom Norrlands kommuner - Donnerberg, Beatrice; Johansson, Linnea (2014)
Most social and economic changes that occur within organizations are the result out of the spread of ideas or phenomena. For this study, it is the spread of accounting innovations with direct or indirect requirement for application among organizations in the public sector that is of interest. The study's research area is focused on this phenomenon based on how the accounting innovation called component depreciation has been spread and adopted in Norrland municipalities. The recommendations from the Council for Municipal Accounting containing information about component depreciation have previously not included any explicit requirement for application of the method. This changed, however, with the new recommendation which will be adopted in 2014, that contains an explicit requirement. The collection of the empirical material for this study has been collected through semi-structured interviews with selected municipalities in northern Sweden. The selection of municipalities is divided into two categories, one includes the municipalities that implemented component depreciation before the new recommendation was adopted and the other includes the municipalities that had not implemented the method yet. The theories that were used in the study consisted of institutional theory and diffusion theory. These theories formed the basis for the analysis of the study's empirical material. The empirical material showed that the majority of municipalities in northern Sweden had not implemented the component depreciation method before it became a requirement even though all respondents from the municipalities claimed that component depreciation is a more accurate way to account for certain assets. In the analysis and the conclusion a couple of factors appeared which affect the adoption of an accounting innovation in the public sector. These factors are resources, routines, laws/requirements and communication. The absence of laws/requirements has been the most prominent reason for organizations to not implement the accounting ...